Menjadi Pembelajar yang Mandiri: Mengungkap Strategi Belajar Bahasa Ingrris secara Ototidak - Pujiani, Tri; Muhammad, Soali; Sukmawati, Ida Dian; Kristanto, Barlian; Putri, Diannike; Krisbiantoro, Benny (Jurnal Pengabdian Masyarakat - PIMAS, 2024)
Self-directed learning has become increasingly important in a dynamic world, with English as the key to global opportunities in education, employment, and cultural exchange. This service activity, conducted at SMK N 1 Purwokerto, aims to encourage students to become autonomous learners in English language acquisition. Through innovative approaches such as lectures, watching short films, and interactive games, students are provided with practical strategies for self-learning. The results of the activity showed an increase in students' motivation and engagement in English learning. Methods such as watching English films have proven effective in enriching vocabulary and improving listening comprehension. Recent studies support the effectiveness of these methods, showing that audiovisual input and the use of subtitles can significantly aid language learning. By providing students with the necessary skills and tools, these activities successfully create a supportive and motivating learning environment, preparing students to become successful independent learners.